2012
DOI: 10.1016/j.actbio.2011.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of gelatin hydrogels incorporating low-molecular-weight heparin for anti-fibrotic therapy

Abstract: The objective of this study is to design biodegradable hydrogels for the controlled release of low-molecular-weight heparin (LMWH) and evaluate the biological activity. Gelatin was cationized by chemically introducing ethylene diamine into the carboxyl groups in different conditions to obtain cationized gelatins. The cationized gelatin was mixed with the LMWH in aqueous solution to form the complex. Gelatin, together with the complex of LMWH and cationized gelatin, was dehydrothermally cross-linked for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…On the other hand, PBS was used as incubation medium to assess the cinnamaldehyde release and degradation process, because release and degradation process are influenced by water absorption in the initial stage . The use of PBS and HCl for accelerated degradation was based on previous research to release and degradation profiles and the validity of such an approach has already been confirmed in the area of polymer sciences …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PBS was used as incubation medium to assess the cinnamaldehyde release and degradation process, because release and degradation process are influenced by water absorption in the initial stage . The use of PBS and HCl for accelerated degradation was based on previous research to release and degradation profiles and the validity of such an approach has already been confirmed in the area of polymer sciences …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there have been several investigations of drug delivery materials demonstrating their feasibility in drug therapy 13) . Some previous reports have shown that DDS technology is necessary to enhance the therapeutic efficacy of various drugs 9,14,15) . In general, the DDS material should be degraded after the drug delivery has been achieved, as the in vivo persistence of delivery materials can induce inflammation and therapeutically unacceptable responses.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation experiment done in this study was referred to some previous studies [8,9,10]. Scaffolds were incubated in NPR-DMEM for 1, 3, 6, 24, 48 and 72 hours.…”
Section: Degradation Experiments In Npr-dmemmentioning
confidence: 99%